Study of epidemiology and management of liver abscess in Jammu region - Iqbal Gulshan, Javaid; Faisal Manzoor, Shahzada (International Journal of Research in Medical Sciences, 2024)
Background: Liver abscess is a common medical condition with different causes and variable morbidity and mortality in different parts of the world, this study has looked into epidemiology, pattern of disease gender and age of affected patients and associated factors. Methods: This prospective study was conducted at a government medical college over a period of one year from August 2022 up to July 2023. Data of patients managed at our centre was collected, analysed and interpreted on MS Excel. Results: The majority of affected patients were male (77.5%). 30 to 40 years age group was the most commonly affected, most of the patients presented with complaints of pain abdomen (85%). Amoebic abscess was present in 71.25% of patients. The right lobe of the liver was involved most commonly (67.5%). Conservative management was successful in 56.25% of patients. Alcohol intake was present in 43.75% of patients, complications were pleural effusion, portal vein thrombosis, necrotizing colitis and gastrointestinal bleeding. Conclusions: In the present era of modern medical science, diagnosis of liver abscesses has become easy through radiological and serological tests, and treatment modalities from minimally invasive to conservative have proved successful in the treatment of liver abscesses. Antibiotics remain the primary course of treatment for both amoebic liver abscess (ALA) and pyogenic liver abscess (PLA), unless there is persistent fever, a substantial abscess cavity, or complications that require surgical intervention. However, challenges persist in combating antibiotic resistance, stemming from incomplete and over-the-counter misuse of available medications. Special concerns include associated comorbidities, delayed medical consultation, and treatment-seeking behavior, as well as the misuse of unhealthy substances or alcohol.